Comparable reliability and acceptability of telepsychiatry and face-to-face psychiatric assessments in the emergency room setting. (1st September 2022) - Bistre, Moises; Juven-Wetzler, Alzbeta; Argo, Daniel; Barash, Igor; Katz, Gregory; Teplitz, Ronen; Said, Muhamad-Musa; Kohn, Yoav; Linkovski, Omer; Eitan, Renana
Abstract: Objective: This study aims to compare the reliability and acceptability of psychiatric interviews using telepsychiatry and face-to-face modalities in the emergency room setting. Methods: In this prospective observational feasibility study, psychiatric patients ( n = 38) who presented in emergency rooms between April and June 2020, went through face-to-face and videoconference telepsychiatry interviews in a non-randomised varying order. Interviewers and a senior psychiatry resident who observed both interviews determined diagnosis, recommended disposition and indication for involuntary admission. Patients and psychiatrists completed acceptability post-assessment surveys. Results: Agreement between raters on recommended disposition and indication for involuntary admission as measured by Cohen's kappa was 'strong' to 'almost perfect' (0.84/0.81, 0.95/0.87 and 0.89/0.94 for face-to-face vs. telepsychiatry, observer vs. face-to-face and observer vs. telepsychiatry, respectively). Partial agreement between the raters on diagnosis was 'strong' (Cohen's kappa of 0.81, 0.85 and 0.85 for face-to-face vs. telepsychiatry, observer vs. face-to-face and observer vs. telepsychiatry, respectively).Psychiatrists' and patients' satisfaction rates, and psychiatrists' perceived certainty rates, were comparably high in both face-to-face and telepsychiatry groups. Conclusions: Telepsychiatry is a reliable and acceptable alternative to face-to-face psychiatric assessments in the emergency room setting. Implementing telepsychiatry may improve the quality and accessibility of mental health services. Key points: Telepsychiatry and face-to-face psychiatric assessments in the emergency room setting have comparable reliability. Patients and providers report a comparable high level of satisfaction with telepsychiatry and face-to-face modalities in the emergency room setting. Providers report a comparable level of perceived certainty in their clinical decisions based on telepsychiatry and face-to-face psychiatric assessments in the emergency room setting.